Economic Sources of Asymmetric Cross-Correlation among Stock Returns - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2001)
We suggest an alternative framework to explain the asymmetric return cross (serial)-correlation. We identify two major sources of the asymmetric cross-correlation: (1) the difference in the sensitivity of stock returns to economic factors, and (2) the differential quality of information between large and small firms. We find that the difference in the response of stock prices to economic factors is an important determinant of the first-order cross-correlation relative to firm-specific factors. Further evidence suggests that the asymmetric cross-correlation is mainly attributed to differences in the sensitivity of stock prices to market-wide information and the differential quality of cash flows information between large and small firms.